SOSIALISASI PENGOLAHAN JAMUR TIRAM MENJADI NUGGET SEBAGAI UPAYA PENINGKATAN EKONOMI MASYARAKAT DESA TAMANSARI WONOREJO PASURUAN - Soedarmadji, Wisma; Maulida, Ade Khofifa; Linsia, Nada Afra; Rochmah, Habibatur; Khasanah, Imarotul; Nurroin, Kavita; Nisa, Khoirun; Hidayah, Reissa Arifa Nur; Saskiyah, Bela Alimatus; Mu’awanah, Cahyatul (Jurnal Abdi Insani, 2024)
White oyster mushroom (Pleurotus ostreatus) is a type of fungus that often grows on agricultural waste in the form of wood or its derivatives. Fungi obtain food from places where they grow and can survive on plant remains around other organisms. Oyster mushrooms are a food commodity that is in great demand among the public, so by cultivating mushrooms it is hoped that they will be able to be involved further, it is hoped that creativity and innovation will emerge and be able to provide added value to society. Oyster mushrooms are only produced and sold fresh without any diversification process. In this KKN activity there will be training on oyster mushrooms to increase family income. As a result of this training, PKK women from Tamansari Wonorejo Village were able to provide understanding and skills to activity participants. PKK women in Tamansari Wonorejo Village have knowledge and skills regarding the food potential around them as an effort to increase family income.